Automated manufacturing process for sustainable prototyping of nuclear magnetic resonance transceivers - S. Wadhwa; S. Wadhwa; N. Wang; K.-M. Reichert; M. Butzer; O. Nassar; M. Jouda; J. G. Korvink; U. Gengenbach; D. Mager; M. Ungerer (Magnetic Resonance, 2025)
Additive manufacturing has enabled rapid prototyping of components with minimum investment in specific fabrication infrastructure. These tools allow for a fast iteration from design to functional prototypes within days or even hours. Such prototyping technologies exist in many fields, including three-dimensional mechanical components and printed electric circuit boards (PCBs) for electrical connectivity, to mention two. In the case of nuclear magnetic resonance (NMR) spectroscopy, one needs the combination of both fields; we need to fabricate three-dimensional electrically conductive tracks as coils that are wrapped around a sample container. Fabricating such structures is difficult (e.g., six-axis micro-milling) or simply not possible with conventional methods. In this paper, we modified an additive manufacturing method that is based on the extrusion of conductive ink to fast-prototype solenoidal coil designs for NMR. These NMR coils need to be as close to the sample as possible and, by their shape, have specific inductive values. The performance of the designs was first investigated using electromagnetic field simulations and circuit simulations. The coil found to have optimal parameters for NMR was fabricated by extrusion printing, and its performance was tested in a 1.05 T imaging magnet. The objective is to demonstrate reproducible rapid prototyping of complicated designs with high precision that, as a side effect, hardly produces material waste during production.